2014
DOI: 10.1155/2014/831054
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic Splenic IDO+Dendritic Cells from the Mice Treated with Induced-Treg Cells Suppress Collagen-Induced Arthritis

Abstract: TGF-β-induced regulatory T cells (iTregs) retain Foxp3 expression and immune-suppressive activity in collagen-induced arthritis (CIA). However, the mechanisms whereby transferred iTregs suppress immune responses, particularly the interplay between iTregs and dendritic cells (DCs) in vivo, remain incompletely understood. In this study, we found that after treatment with iTregs, splenic CD11c+DCs, termed “DCiTreg,” expressed tolerogenic phenotypes, secreted high levels of IL-10, TGF-β, and IDO, and showed potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Previous studies demonstrated the potential of CD11b + DCs to ameliorate CIA . We therefore, examined the potential of a newly produced CD11b + DC line to exert an immune regulatory effect in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated the potential of CD11b + DCs to ameliorate CIA . We therefore, examined the potential of a newly produced CD11b + DC line to exert an immune regulatory effect in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…At baseline, intratumoral TAMs were M2 polarized as assessed by arginase to inducible nitric oxide ratio (data not shown). We next examined the expression of TGF-beta which both induces and is produced by Tregs and TAMs (reviewed in (33, 34)), is produced by IDO expressing dendritic cells (35) and is also known to block lymphocyte activation (36). All of the therapies reduced TGF-beta expression relative to control but this was most pronounced and most significant in the triple combination (Figure 4C, p<0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…IDO expression has been linked to a tolerogenic DC phenotype, associated with decreased expression of CD80 and MHC II and increased TGF-beta production (35). No change in DC numbers or activation within dLNs was observed (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Upon inflammation, IDO production has been shown to compromise T cell proliferation, promote T cell anergy and Tregs [24], [25], [26]. Depending on the experimental context, IDO can be induced either by IFN-γ, IFN-α/β, or TGF-β.…”
Section: Introductionmentioning
confidence: 99%